Critical elements in nursing graduates' transition to advanced practice roles and their perceived impact on patient care: an exploratory, descriptive study of graduates' and their managers' perceptions - Janita P. C. Chau; Suzanne H. S. Lo; Simon K. Y. Lam; Ravneet Saran; David R. Thompson (BMC, 2022)
Abstract Background While there is a growth in the number of advanced practice nurses, there is a dearth of research examining their role transition from registered nurses. This study aimed to identify critical elements in the career path of nursing graduates who have taken up advanced practice roles and examine their perceived impact on patient care. Methods An exploratory descriptive study was performed. Individual semi-structured interviews were conducted face-to-face with 10 nursing graduates now in advanced practice roles, and their ten respective managers. All interviews were audio-recorded and transcribed verbatim for latent and manifest content analyses. Results The nursing graduates, six of whom were male, had a mean age of 35 years. All possessed a master's degree and formal post-registration education and/or training. Six had at least three years' experience as an advanced practice nurse. The managers, all female, had a mean age of 49 years. Eight had at least one year's experience in their current position. Six key themes emerged: prior enhancement of personal and professional knowledge and skills; active participation in clinical roles and knowledge translation in preparation for advanced practice; adapting to new and diverse advanced practice nursing responsibilities; role of advanced practice nurses in leadership; personal qualities crucial for success in advanced practice; and provision of evidence-based patient-centered care. Conclusions Postgraduate education, management knowledge and leadership skills, and active participation in clinical roles and knowledge translation appear crucial ingredients for promotion of nursing graduates to advanced practice roles. Other ingredients include a positive outlook, flexibility and adaptability, and good interpersonal, communication and problem-solving skills.